Eocene to Oligocene vegetation and climate in the Tasmanian Gateway region were controlled by changes in ocean currents and p CO 2 - M. Amoo; U. Salzmann; M. J. Pound; N. Thompson; P. K. Bijl (Climate of the Past, 2022)
Considered one of the most significant climate reorganizations of the Cenozoic period, the Eocene–Oligocene Transition (EOT; ca. 34.44–33.65) is characterized by global cooling and the first major glacial advance on Antarctica. In the southern high latitudes, the EOT cooling is primarily recorded in the marine realm, and its extent and effect on the terrestrial climate and vegetation are poorly documented. Here, we present new, well-dated, continuous, high-resolution palynological (sporomorph) data and quantitative sporomorph-based climate estimates recovered from the East Tasman Plateau (ODP Site 1172) to reconstruct climate and vegetation dynamics from the late Eocene (37.97 Ma) to the early Oligocene (33.06 Ma). Our results indicate three major climate transitions and four vegetation communities occupying Tasmania under different precipitation and temperature regimes: (i) a warm-temperate Nothofagus –Podocarpaceae-dominated rainforest with paratropical elements from 37.97 to 37.52 Ma; (ii) a cool-temperate Nothofagus -dominated rainforest with secondary Podocarpaceae rapidly expanding and taking over regions previously occupied by the warmer taxa between 37.306 and 35.60 Ma; (iii) fluctuation between warm-temperate–paratropical taxa and cool temperate forest from 35.50 to 34.49 Ma, followed by a cool phase across the EOT (34.30–33.82 Ma); and (iv) a post-EOT (earliest Oligocene) recovery characterized by a warm-temperate forest association from 33.55 to 33.06 Ma. Coincident with changes in the stratification of water masses and sequestration of carbon from surface water in the Southern Ocean, our sporomorph-based temperature estimates between 37.52 and 35.60 Ma (phase ii) showed 2–3 ∘ C terrestrial cooling. The unusual fluctuation between warm and cold temperate forest between 35.50 to 34.59 Ma is suggested to be linked to the initial deepening of the Tasmanian Gateway, allowing eastern Tasmania to come under the influence of warm water associated with the proto-Leeuwin Current (PLC). Further to the above, ...